Crystal Structures and Proton Conductivities of a MOF and Two POM–MOF Composites Based on CuII Ions and 2, 2′‐Bipyridyl‐3, 3′‐dicarboxylic Acid1. Issue 5 (13th December 2012) - Wei, Meilin; Wang, Xiaoxiang; Duan, Xianying
Abstract We have succeeded in constructing a metal–organic framework (MOF), [Cu(bpdc)(H2O)2]n (H2bpdc=2, 2′‐bipyridyl‐3, 3′‐dicarboxylic acid, 1), and two poly‐POM–MOFs (POM=polyoxometalate), {H[Cu(Hbpdc)(H2O)2]2[PM12O40]⋅n H2O}n (M=Mo for 2, W for 3), by the controllable self‐assembly of H2bpdc, Keggin‐anions, and Cu2+ ions based on electrostatic and coordination interactions. Notably, these three compounds all crystallized in the monoclinic space group P21/n, and the Hbpdc− and bpdc2− ions have the same coordination mode. Interestingly, in compounds 2 and 3, Hbpdc− and the Keggin‐anion are covalently linked to the transition metal copper at the same time as polydentate organic ligand and as polydentate inorganic ligand, respectively. Complexes 2 and 3 represent new and rare examples of introducing the metal N‐heterocyclic multi‐carboxylic acid frameworks into POMs, thereby, opening a pathway for the design and the synthesis of multifunctional hybrid materials based on two building units. The Keggin‐anions being immobilized as part of the metal N‐heterocyclic multi‐carboxylic acid frameworks not only enhance the thermal stability of compounds 2 and 3, but also introduce functionality inside their structures, thereby, realizing four approaches in the 1D hydrophilic channel used to engender proton conductivity in MOFs for the first time. Complexes 2 and 3 exhibit good proton conductivity (10−4 to ca. 10−3 S cm−1) at 100 °C in the relative humidity range 35 to about 98 %.